The Geochemical Evolution of Santa Cruz Island, Galápagos Archipelago - Wilson, E. L.; Harpp, K. S.; Schwartz, D. M.; Van Kirk, R. (Frontiers in Earth Science, 2022)
Understanding how ocean island volcanoes evolve provides important insight into the behavior of mantle plumes, how plumes interact with mid-ocean ridges, and potential risks posed to inhabitants as the islands age. In this field-based study of the Galápagos Islands, we use radiogenic isotope ratio, major element, and trace element analysis of >70 new lava samples to document the geochemical evolution of Santa Cruz Island over the past ∼2 million years, as it has been carried away from the plume. Currently, Santa Cruz is a dormant shield volcano in the central archipelago. Previous work indicates that exposed lavas preserve >1 million years of activity in two eruptive units: 1) The older Platform Series, exposed primarily in the northeast; and 2) the Shield Series, which blankets the rest of Santa Cruz and erupted from a WNW trending fissure system. Our new geochemical analyses indicate that the Platform Series lavas are more evolved and isotopically enriched than Shield lavas, but neither as compositionally monotonous nor as isotopically enriched as the younger western Galápagos volcanoes. Santa Cruz formed when the Galápagos Spreading Center (GSC) was closer to the plume than it is today, resulting in enhanced plume-ridge interaction and transport of plume material to the ridge. Consequently, the Platform Series was formed under relatively magma-starved conditions compared to today’s western volcanoes. Magma supply was sufficient for partial fractionation and homogenization of melts in shallow reservoirs, but inadequate to support thermochemically buffered networks like those in the present-day western archipelago. The slight depletion of Platform Series lavas relative to Fernandina reflects entrainment of depleted upper mantle and/or diversion of deep, enriched plume melts to the nearby GSC. The younger Shield Series lavas are even more depleted because plate motion has carried the volcano across the compositional boundary of the bilaterally asymmetric plume into its more depleted zone. Shield Series lavas’ variable, primitive compositions reflect minimal crustal processing in small, ephemeral, poorly supplied magma reservoirs. Unlike the young western shields, the constructional history of Santa Cruz has been controlled to a significant extent by its proximity to the GSC.